"I'm Principled Against Slavery, but …": Colorblindness and the Three-Fifths Debate. (1st June 2017) - Henricks, Kasey
Abstract: No longer is it acceptable to rationalize racial hierarchy in explicit terms. Today's racism substitutes these views for seemingly nonracial ones that diminish structural discrimination and "blame the victim." Though recent studies uncover the subtle, implicit, and covert discourse of colorblindness, claims of ideological progression have been offered without empirical verification. Examining debate surrounding the three-fifths clause of the U.S. Constitution, I complete a historical ethnographic content analysis that transplants colorblind ideology into historical soil where some presume it does not belong. The data derive from A Century of Lawmaking for a New Nation, which is an archival collection held by the Library of Congress. The data set consists of 1, 493 pages of congressional record. My findings reveal how colorblindness captured in phrases like "I'm not racist, but …." have historical parallels in "I'm principled against slavery, but …" This observation merits more theoretical attention because it shows how the very ideology some describe as novel today persisted in a previous era. In other words, colorblindness was not created out of whole cloth in post-1960s America.